Nectin-4 is a breast cancer stem cell marker that induces WNT/β-catenin signaling via Pi3k/Akt axis. (August 2017) - Siddharth, Sumit; Goutam, Kunal; Das, Sarita; Nayak, Anmada; Nayak, Deepika; Sethy, Chinmayee; Wyatt, Michael D.; Kundu, Chanakya Nath
Highlights: Nectin-4 is a marker for breast cancer stem cells. Nectin-4 − upregulates, EMT, metastasis and WNT/β-Catenin pathway via Pi3k/Akt axis. Nectin-4 depletion inhibited EMT, metastasis, invasion and WNT/β-Catenin pathway. Clinicopathological data show induced Nectin-4 in breast tumor metastases to axillary lymph node. Abstract: Nectin-4 is well known as a junction protein. Recent reports have implicated it in cancer, but there has been little exploration of its functional significance in metastasis and cancer stem cells. Here, using the breast cancer metastasis model system, we report Nectin-4 is a marker for breast cancer stem cells (BCSCs) and provide experimental evidence suggesting that it utilizes WNT/β-Catenin signaling via Pi3k/Akt axis for self renewal of BCSCs. In vitro, in vivo, ex vivo and clinical pathological data showed upregulated Nectin-4 in breast cancer metastasis and WNT/β-Catenin signaling. Nectin-4 depletion inhibited EMT, metastasis, invasion, and the WNT/β-Catenin pathway; conversely, Nectin-4 overexpression in null cells upregulated EMT and metastasis and also induced WNT/β-Catenin signaling via Pi3k/Akt axis, which in turn, controls cancer stem cell proliferation. Induced Nectin-4 was observed in breast tumor patient samples and in breast tumor metastases to axillary lymph nodes, which indicated that Nectin-4 is not only a BCSC marker but also a breast cancer metastasis marker. The current study provides clear evidence that Nectin-4 is a BCSC marker and is responsible for breast cancer metastasis.